CLIMATE OF MOSCOW AND ITS LONG-TERM CHANGES (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The changes of Moscow climate over 245 years of regular meteorological observations have been studied. It is shown that, on average, over the entire period from 1780 to 2024, the air temperature (Т) on the urban periphery increased at a rate of 0.012℃/year, and in the center of Moscow – at a rate of 0.017℃/year, which is partially due to the influence of the urban "heat island". In the background rural area of the Moscow Region at the latitude of Moscow, Т increased by no less than 1.5℃: probably by 2.0℃ over 245 years. Warming is stronger in the winter and spring months: the excess of the modern climatic norm for the period 1991–2020 compared to the conditions of the late XVIII century is statistically significant from December to April and on October. As a result, the amplitude of the annual air temperature cycle and the degree of continentality of the Moscow climate are gradually decreasing. No stable cyclicality with periods longer than a year was detected in the changes of Т.
Keywords: climate changes; early meteorological observations; Little Ice Age; climate norm; statistical significance; continentality of climate